2017
DOI: 10.3390/f8060194
|View full text |Cite
|
Sign up to set email alerts
|

Preserving Ecosystem Services on Indigenous Territory through Restoration and Management of a Cultural Keystone Species

Abstract: Eastern white pine (Pinus strobus L.) is a cultural keystone tree species in the forests of eastern North America, providing numerous ecosystem services to Indigenous people. White pine abundance in the landscape has considerably decreased over the last few centuries due to overharvesting, suppression of surface fires, extensive management, and plantation failure. The Kitcisakik Algonquin community of western Quebec is calling for restoration and sustainable management of white pine on its ancestral territory,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 53 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…Some authors concluded that the inherent value in the cultural keystone species concept is merely a process of exploration rather than the quantification of cultural significance [30], and others have continued to support the idea that it is useful tool for conservation and restoration [84]. Whether researchers employ qualitative, quantitative, or interdisciplinary methodologies for keystone designation it is clear there are inherent limitations, potential biases, as well as advantages in all of these approaches.…”
Section: Call For Actionmentioning
confidence: 99%
“…Some authors concluded that the inherent value in the cultural keystone species concept is merely a process of exploration rather than the quantification of cultural significance [30], and others have continued to support the idea that it is useful tool for conservation and restoration [84]. Whether researchers employ qualitative, quantitative, or interdisciplinary methodologies for keystone designation it is clear there are inherent limitations, potential biases, as well as advantages in all of these approaches.…”
Section: Call For Actionmentioning
confidence: 99%
“…As local, peasant, traditional, and indigenous forms of ecological knowledge, hereafter traditional ecological knowledge (TEK), are increasingly documented, validated and valued, the search for synergies between TEK and environmental sciences has exploded [9,15]. The instrumental potential of TEK for improving conservation, restoration and resource management sustainability is largely recognized [8,16,17]. As pervasive environmental and social crises have exposed the limitations of science and technology, other rationalities and alternative worldviews are pointed to as a potential source of solutions to those crises [18][19][20], leading environmental scientists to increasingly adopt more holistic approaches [13,21], some of which embrace TEK [20,22,23].…”
Section: Setting the Scene: Cfm And Tekmentioning
confidence: 99%
“…Alternatively, an increase in the demand for NPrES and increased environmental regulation (stricter policies and better enforcement) may cause the social license for extraction to be removed (Prno and Slocombe 2012). The increase in the demand for NPrES may also increase the capacity and involvement of Indigenous communities, as Indigenous culture places high value around NPrES in Traditional Knowledge and land uses, which is argued to be essential to sustainable forestry (Huntington 2000;Beaudoin et al 2015;Uprety et al 2017). Increases in the demand for both PrES and NPrES have the potential to lead to more sustainable policies because of overlapping needs (Davies and Mazumder 2003), but more often than the focus is on developing PrES over NPrES (Raudsepp-Hearne et al 2010;Zheng et al 2016).…”
Section: Pres and Npresmentioning
confidence: 99%